DIAGNOSTICS WITH TUBERCULIN IN CHILDREN IN MODERN CONDITIONS - E.A. Borodulina; E.A. Amosova; B.E. Borodulin; M.V. Galiley ("Paediatrician" Publishers LLC, 2010)
The literature review is dedicated to the characteristics of methods of diagnostics with tuberculin and the problems of contamination with mycobacterium tuberculosis in conditions of mass vaccinations of children with BCG. Key words: children, tuberculin, Mantoux test, contamination, mycobacterium tuberculosis. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):70-74)